Uses of curculigo latifolia (C.latifolia) extracts - Ismail, Maznah; Ishak, Nur Akmal; Hamid, Muhajir (2011)
The present invention relates to Curculigo latifolia (C.latifolia) extracts, wherein the extracts extracted from different parts of a plant such as fruits, roots and leaves, individually and in any combination thereof, characterized in that the extracts are used as an agent for treating and preventing metabolic disorder disease such as diabetes mellitus, obesity, cardiovascular, and atherosclerosis.